2018
DOI: 10.1002/asia.201801083
|View full text |Cite
|
Sign up to set email alerts
|

Triamterene‐Grafted Graphitic Carbon Nitride with Electronic Potential Redistribution for Efficient Photocatalytic Hydrogen Evolution

Abstract: In this study, a photocatalyst with a distorted skeleton and synthesized by grafting triamterene onto graphitic carbon nitride (g-C N ) frameworks was prepared. The pteridine ring of the triamterene-based nitrogen-enriched organic structure functions as a trapped electron site owing to its inductive effect. The benzene ring in triamterene plays an important role in the even dispersion of electrons by a conjugative effect. Redistribution of the intramolecular electronic potential is caused by a synergistic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In order to explore the charge transmission between UCN and AB or APy, electrochemical impedance spectroscopy (EIS) of the above samples in the dark was studied and the spectra are depicted in Figure d. It can be observed that UCN‐APy exhibits the smallest radius, representing the smallest charge transfer resistance, followed by UCN‐AB and UCN. This is in line with the above data.…”
Section: Resultsmentioning
confidence: 99%
“…In order to explore the charge transmission between UCN and AB or APy, electrochemical impedance spectroscopy (EIS) of the above samples in the dark was studied and the spectra are depicted in Figure d. It can be observed that UCN‐APy exhibits the smallest radius, representing the smallest charge transfer resistance, followed by UCN‐AB and UCN. This is in line with the above data.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, an additional peak for UCN-5TDA appears at $114.4 ppm, corresponding to the existence of aromatic C]C from TDA. 39,40 In addition, the solid-state 1 H NMR spectra of UCN and UCN-5TDA were analyzed. As shown in…”
Section: Phase Structure Morphology and Surface Chemical Statementioning
confidence: 99%
“…Graphitic CN, a metal-free polymeric photocatalyst, is formed by repeating triazine units with π-conjugated systems. In view of the unique electronic and optical properties ( E g = 2.7 eV, active under ultraviolet and a portion of visible light), high thermal, chemical, and optical stability, graphitic CN has been demonstrated to be an outstanding visible-light-driven photocatalyst to generate hydrogen from water. During the photocatalytic process, cocatalysts based on noble metals such as Pt and Pd, are usually necessary to promote the separation of photogenerated carriers and reduce the hydrogen evolution overpotential. , Consequently, various strategies, such as controlling morphologies, combining with molecular dopants, or constructing heterojunction structures, have been approved to enhance the photocatalytic activity of CN. Nevertheless, the utilization of noble metals still suppresses the application of CN for hydrogen generation.…”
Section: Introductionmentioning
confidence: 99%